Implementasi Pendekatan Kontekstual dalam Menanamkan Nilai Pendidikan Islam di Madrasah Ibtidaiyah Nurul Ummah Yogyakarta - Syakur Wildan; Itmam Mutaqien; Tasman Hamami (ISLAMIKA, 2023)
Islamic education is an attempt to provide human qualities by having a consistent sense of being a Muslim. Now Islamic education is far from the desired expectation, one of which is declining morals. The decline in morals is the impact of a very large problem and has an effect on the value of Islamic education resources. This must be done in a way to minimize the above problems so that the value of Islamic education resources can provide the common good. Contextual approach as an effort to provide a link to the quality of Islamic education values. The research method used is descriptive qualitative approach with a sample of Madrasah Ibtidaiyah Nurul Ummah students. The researchers' data collection techniques were interviews and observations, while the data analysis was in the form of data reduction, data presentation, and verification. The result of the discussion in this article is that the value of Islamic education with a contextual approach greatly impacts students. That's because contextual learning can help students understand the subject matter they are studying by connecting the subject matter with its application in everyday life, a teacher must provide good education to students to apply the values of monotheism and moral values that exist within themselves. . Thus, the way that can be done in implementing the values of Islamic education with a contextual approach is by creating meaningful relationships, carrying out meaningful activities, working on independent arrangements in learning activities, cooperating, and guiding students to apply critical and creative attitudes to learning activities. his way of thinking.